The eight oldest geomagnetic observatories in China - Jinping Zhou (地震科学进展)
This paper describes the history of the establishing eight pioneering geomagnetic observatories and how they were essential in building the foundation of China’s subsequent geomagnetic network. This development filled the historical gap of geomagnetic stations in key regions of China and laid a solid foundation for further geomagnetic research and development in China. The content of this paper is comprehensive and detailed, possessing both historical value and scientific popularization.